“MÉTODO COLABORATIVO EN EL INTER-APRENDIZAJE DE ECUACIONES LINEALES, EN LOS ESTUDIANTES DE SEGUNDO DE BACHILLERATO DE LA UNIDAD EDUCATIVA SAN GERARDO, PERIODO OCTUBRE 2018- MARZO 2019” - Chicaiza Chicaiza, Luis Fausto (2019)
The research was carried out with the objective, the performance of the students was determined, the second, the collaborative method was used in de interpretation of linear equations, period October 2018 – March 2019. Part of the problem about teaching learning of linear equations the theoretical topics related to the subject. The research is of a non- experimental nature and the variables are not deliberately manipulated: collaborative method the and inter-learning of linear equation. That is, it is a research where the independent variable was not intentionally varied for the collaborative work method. Simply observe the phenomena as they occurred in their natural context. By talking the generalities of knowledge, we came to infer the conclusions of their behavior, as well as the advantages of using the collaborative method in its three dimensions, cognitive, procedural and attitudinal, from then for the conclusions and recommendations. Definitive use of the collaborative method in its three dimensions is an effective way to learn the contents of linear equations and serves as a fundamental means for the development of skills in the group, achieving greater participation and an effective classroom environment.